Chitin-derived polymer deacetylation regulates mitochondrial reactive oxygen species dependent cGAS-STING and NLRP3 inflammasome activation. (August 2021) - Turley, Joanna L.; Moran, Hannah B.T.; McEntee, Craig P.; O'Grady, Katie; Muñoz-Wolf, Natalia; Jin, Lei; Follmann, Frank; Andersen, Peter; Andersson, Mats; Lavelle, Ed C.
Abstract: Chitosan is a cationic polysaccharide that has been evaluated as an adjuvant due to its biocompatible and biodegradable nature. The polysaccharide can enhance antibody responses and cell-mediated immunity following vaccination by injection or mucosal routes. However, the optimal polymer characteristics for activation of dendritic cells (DCs) and induction of antigen-specific cellular immune responses have not been resolved. Here, we demonstrate that only chitin-derived polymers with a high degree of deacetylation (DDA) enhance generation of mitochondrial reactive oxygen species (mtROS), leading to cGAS-STING mediated induction of type I IFN. Additionally, the capacity of the polymers to activate the NLRP3 inflammasome was strictly dependent on the degree and pattern of deacetylation and mtROS generation. Polymers with a DDA below 80% are poor adjuvants while a fully deacetylated polyglucosamine polymer is most effective as a vaccine adjuvant. Furthermore, this polyglucosamine polymer enhanced antigen-specific Th1 responses in a NLRP3 and STING-type I IFN-dependent manner. Overall these results indicate that the degree of chitin deacetylation, the acetylation pattern and its regulation of mitochondrial ROS are the key determinants of its immune enhancing effects.